Linking the "recovery and resilience plan" and smart specialisation: The Portuguese case - Anabela Marques Santos (European Commission, Joint Research Centre (JRC), 2021)
Based on the case study of Portugal, the present study aims to analyse the alignment of investments in the Portuguese "Recovery and Resilience Plan" with the Smart Specialisation Strategies priorities (2021-2027) of this territory, and then identify opportunities for potential synergies and complementary between funding instruments. With the information available in the Plan and its annex, a detailed analysis is performed to identify investments able to enhance Research & Development, and Innovation and/or to improve the regional innovation ecosystems. The analysis shows that up to exteuro6 Billion of the Plan (37%) may potentially support directly and indirectly the Smart Specialisation in Portugal. However, the effect of such contribution will strongly depend on the final beneficiaries, projects selected, absorption capacity, and governance model. The paper also explains the relevance of Smart Specialisation in the Covid-19 recovery and draft some policy recommendations.
Keywords: E32; O31; G38; 330; Covid-19 crisis; Innovation; Government Policy; Portugal